2014
DOI: 10.1155/2014/480947
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis and X-Linked Agammaglobulinemia: An Uncommon Association

Abstract: Introduction. X-linked agammaglobulinemia (XLA) is a primary immunodeficiency characterized by agammaglobulinemia requiring replacement treatment with immunoglobulin. The association of XLA and membranoproliferative glomerulonephritis (MPGN) is unexpected and, to our knowledge, only one case was previously published. Case Report. The authors report the case of a 10-year-old boy with family history and prenatal diagnosis of XLA, treated from birth with intravenous immunoglobulin replacement therapy. He presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[10] The most common autoimmune disorders in primary antibody deficiencies are immune thrombocytopenic purpura and autoimmune hemolytic anemia. [11] Moreover, other diseases including autoimmune thyroid disease, [12] type 1 diabetes, [13] rheumatoid arthritis, [14] SLE, [15] dermatomyositis, [16] inflammatory bowel diseases, [17] alopecia areata, [15] vitiligo, [12] and glomerulonephritis [18] are also common in primary antibody deficiencies due to the lack of self-tolerance. [19]…”
Section: Discussionmentioning
confidence: 99%
“…[10] The most common autoimmune disorders in primary antibody deficiencies are immune thrombocytopenic purpura and autoimmune hemolytic anemia. [11] Moreover, other diseases including autoimmune thyroid disease, [12] type 1 diabetes, [13] rheumatoid arthritis, [14] SLE, [15] dermatomyositis, [16] inflammatory bowel diseases, [17] alopecia areata, [15] vitiligo, [12] and glomerulonephritis [18] are also common in primary antibody deficiencies due to the lack of self-tolerance. [19]…”
Section: Discussionmentioning
confidence: 99%
“…The most common autoimmune disorders in PADs are immune thrombocytopenic purpura (ITP) and autoimmune hemolytic anemia (AIHA) [7]. Moreover, other diseases including autoimmune thyroid disease [8], type 1 diabetes (T1D) [9], rheumatoid arthritis (RA) [10], systemic lupus erythematosus (SLE) [11], dermatomyositis [12], inflammatory bowel diseases (IBD) [13], alopecia areata [11], vitiligo [8], and glomerulonephritis [14] are also common in PADs due to the lack of self-tolerance [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite XLA patients exhibiting low serum immunoglobulin concentrations and defective antibody responses, they have an increased risk of developing autoimmune diseases such as juvenile idiopathic arthritis, juvenile dermatomyositis, inflammatory bowel disease, and Kawasaki disease [ 3 , 4 ]. Renal involvement in XLA is rarely observed, and previous studies have reported instances of membranoproliferative glomerulonephritis (MPGN) and membranous glomerulopathy (MG) in XLA patients receiving intravenous immunoglobulin (IVIG) therapy [ 5 7 ]. In this present study, we describe the first case of immunoglobulin (Ig) A nephropathy associated with XLA.…”
Section: Introductionmentioning
confidence: 99%